Ultrasound microbubble-mediated RNA interference targeting WNT1 inducible signaling pathway protein 1(WISP1) suppresses the proliferation and metastasis of breast cancer cells. Issue 4 (1st April 2022) - Fang, Faying; Xu, Weizhi; Zhang, Jian; Gu, Jin; Yang, Gaoyi
ABSTRACT: In the context of relatively sufficient research that annotated WNT1 inducible signaling pathway protein 1 (WISP1) as a promoting factor in tumor progression of breast cancer, and identified the effects of ultrasound microbubble technology on enhancing the transfection efficiency and achieving better gene interference, this study managed to investigate the effects of ultrasound microbubble-mediated siWISP1 transfection on proliferation and metastasis of breast cancer cells. To achieve our research objectives, the expression of WISP1 in breast cancer tissues was retrieved from GEPIA website, and the viability of breast cancer cells (SK-BR-3 and MCF7) was assessed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay for ultrasound intensity screening. After the transfection of siWISP1 by ultrasound microbubble or lipofectamine 6000, the content of WISP1 secreted by cells was detected through Enzyme-linked immunosorbent assay (ELISA), and WISP1 expression in cells was determined by quantitative reverse transcription polymerase-chain reaction (qRT-PCR). Besides, the cell invasion, migration, and proliferation were evaluated by wound healing, transwell, and EdU assays, respectively. In accordance with experimental results, WISP1 was highly expressed in breast cancer tissues, and the 1 W/cm 2 intensity was the onset of a notable decrease in cell viability. Compared with lipofectamine 6000 transfection, the transfection of siWISP1 mediated by ultrasound microbubble further reduced the expression of WISP1, and meanwhile suppressed cell invasion, migration, and proliferation. Collectively, ultrasound microbubble-mediated transfection of siWISP1 worked rather effectively in improving transfection efficiency and inhibiting the progression of breast cancer. Graphical abstract: uf0001